2020
DOI: 10.1029/2019jb018547
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Influence of Fracture Density on Network Scale Transport

Abstract: The topology of natural fracture networks is inherently linked to the structure of the fluid velocity field and transport therein. Here we study the impact of network density on flow and transport behaviors. We stochastically generate fracture networks of varying density and simulate flow and transport with a discrete fracture network model, which fully resolves network topology at the fracture scale. We study conservative solute trajectories with Lagrangian particle tracking and find that as fracture density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…Sherman et al. (2020) discussed the tortuosity effect in detail and concludes that honoring the tortuosity distribution can improve model performance. Our results show that using an average tortuosity value is sufficient to capture overall transport behavior.…”
Section: Upscaled Stochastic Transport Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Sherman et al. (2020) discussed the tortuosity effect in detail and concludes that honoring the tortuosity distribution can improve model performance. Our results show that using an average tortuosity value is sufficient to capture overall transport behavior.…”
Section: Upscaled Stochastic Transport Modelmentioning
confidence: 99%
“…Many studies in the literature (Benke & Painter, 2003; Hyman et al., 2019b; Kang, Brown, et al., 2016; Le Borgne et al., 2008; Sund et al., 2016) have shown that the Lagrangian velocity series { v n }, if sampled in space, can be modeled as Markov processes. These observations have led to the development of CTRW formulations based on velocity Markov models (Dentz et al., 2016; Hakoun et al., 2019a; Kang et al., 2017; Le Borgne et al., 2008) that are able to predict anomalous transport in porous and fractured media (Comolli et al., 2019; Hyman et al., 2019b; Kang, Brown, et al., 2016; Kang et al., 2014; Le Borgne et al., 2008; Sherman et al., 2020; Sund et al., 2016). The empirical estimation of the transition matrix, equation (), from numerical or experimental data can be a challenging issue in practice (Sherman et al., 2017).…”
Section: Upscaled Stochastic Transport Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This multiscale structural heterogeneity leads to multiscale flow channelization at length scales ranging from the entire system down to the subfracture size. At the largest scale, network density and connectivity alter the distribution of flow within the network, but this connection has only been qualitatively identified at this time (Huseby et al., 2001; Hyman & Jiménez‐Martínez, 2018; Hyman et al., 2019a; Sherman et al., 2020; Sweeney & Hyman, 2020). While it is generally accepted that a lower degree of flow channeling ought to occur in higher‐density networks, how to quantify the degree of flow channeling and link those measurements to geological features remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sherman et al. (2020) observed that network density affected flow channeling and then studied the ability of upscaled transport models to reproduce high‐fidelity transport simulations using DFN models at these various densities. However, they did not systematically study the link between network structure attributes and flow channel formation nor develop new methods to compare flow channelization between networks.…”
Section: Introductionmentioning
confidence: 99%